Seed Maturity Indices in Silver Fir (Abies pindrow Spach) - Singh, Ombir (Indian Forester, 1998)
This study deals with seed maturity of Silver fir in relation to specific gravity of cones and seed moisture content. The specific gravity of mature cones varied from 0.97 to 0.98 and germination percentage of the seed collected from such cones was about 32%. The moisture content of the seed decreased as the seed matured and the same of the mature seed varied from 15.82 to 16.60 per cent.